On the existence of free-surface azimuthal equatorial flows. Issue 7 (19th May 2017) - Martin, Calin Iulian
Abstract : This paper is concerned with the governing equations (together with the free boundary and the bottom boundary conditions) for an inviscid, incompressible fluid, written in spherical coordinates which are fixed at a point on the rotating Earth. For a special type of a steady flow moving only in the azimuthal direction, with no variation in this direction, we provide a functional-analytic study of the link between the pressure at the free surface of the ocean and the distortion of that surface.